Cross-dehydrogenative coupling for the intermolecular C–O bond formation - Krylov, Igor B; Vil’, Vera A; Terent’ev, Alexander O (Beilstein journal of organic chemistry, 2015)
The present review summarizes primary publications on the cross-dehydrogenative C–O coupling, with special emphasis on the studies published after 2000. The starting compound, which donates a carbon atom for the formation of a new C–O bond, is called the CH-reagent or the C-reagent, and the compound, an oxygen atom of which is involved in the new bond, is called the OH-reagent or the O-reagent. Alcohols and carboxylic acids are most commonly used as O-reagents; hydroxylamine derivatives, hydroperoxides, and sulfonic acids are employed less often. The cross-dehydrogenative C–O coupling reactions are carried out using different C-reagents, such as compounds containing directing functional groups (amide, heteroaromatic, oxime, and so on) and compounds with activated C–H bonds (aldehydes, alcohols, ketones, ethers, amines, amides, compounds containing the benzyl, allyl, or propargyl moiety). An analysis of the published data showed that the principles at the basis of a particular cross-dehydrogenative C–O coupling reaction are dictated mainly by the nature of the C-reagent. Hence, in the present review the data are classified according to the structures of C-reagents, and, in the second place, according to the type of oxidative systems. Besides the typical cross-dehydrogenative coupling reactions of CH- and OH-reagents, closely related C–H activation processes involving intermolecular C–O bond formation are discussed: acyloxylation reactions with ArI(O 2 CR) 2 reagents and generation of O-reagents in situ from C-reagents (methylarenes, aldehydes, etc.).